The evaluation of potential dietary media, measurement parameters and storage techniques for use in forensic entomotoxicology - Mbatha, Erica Isabel Tavares Da Silva (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
The term forensic entomotoxicology was coined by Pounder and is used to describe the process of using insects to determine the presence or absence of toxicants in decomposing corpses. Forensic entomotoxicology is most applicable when the orthodox sources of evidence (i.e. blood and urine) are no longer available for testing due to the degree of putrefaction as a result of the decomposition process. As the field is relatively new, various authors have conducted studies to determine the effects of different toxicants on different insects. These studies have all been conducted in the absence of a standardised protocol and we hypothesise that this has led to conflicting results (i.e. two different authors will conduct a study using the same toxicant and model insect and the effects on the insects will differ significantly). The aim of this thesis was to identify the areas which might have led to the artefacts in the results and identify ways in which to standardise them. The three areas selected were the feeding substrates and the measures taken to quantify growth rate, as well as the preservation techniques that should be used for preserving larval flies. The recommendation from the literature review was that artificial diets would be the most appropriate dietary media to use for entomotoxicological studies. An artificial diet was selected and modified for potential used in entomotoxicological studies. Four different diets (no meat treatment, fish, beef and pork artificial diets) were used to rear Chrysomya chloropyga larvae and their growth rates were measured using length and width. The fly larvae reared on the fish and no meat treatment diets did not reach pupation stage. The beef and pork diets produced the largest larvae and the flies in these treatments reached adult stage. The recommendation was that the beef and pork treatments be tested with various toxicants to establish their stability in the matrix and the diet that provides the toxicants with the most stability should be used for future entomotoxicological studies. The two other factors selected for standardisation were the parameters used to quantify growth rate, as well as the preservation techniques used to store empty Chrysomya chloropyga pupal casings and Calliphora croceipalpis third instar larvae. Previous authors have suggested that width be used as an alternative to length to quantify growth rate. The results from this thesis show that length should continue to be used as the standard parameter because the incremental change in length is much larger than the change in width, and these larger increments allow for greater resolution when estimating the age of the larvae. Various authors have also suggested that pupal casings should be stored without any preservative, whereas fly larvae should be stored in concentrations of ethanol >70%. The results in this thesis have shown that the concentration of ethanol does not make any significant difference to the proportional change of length and width of the empty pupal casings and the third instar larvae. The recommendation is that when selecting the preservation technique, the integrity of the specimen for examination of other evidence (i.e. DNA or toxicological extraction) should take precedence. Although this thesis has not completely standardised the protocol for forensic entomotoxicology, it has indicated the areas that need to be focused on in order for standardisation to occur. Future studies should focus on standardisation, as this makes studies more comparable and ultimately makes entomotoxicological evidence admissible in the court of law.
Keywords: Blowflies -- Feeding and feeds; Blowflies -- Larvae; Blowflies -- Physiology; Blowflies -- Collection and preservation; Poisons -- Analysis; Death -- Causes; Forensic pathology; Forensic entomology; Forensic entomotoxicology